Formation mechanism of Pickering emulsion gels stabilized by proanthocyanidin particles: Experimental and molecular dynamics studies - Sheng Geng; Fenxia Han; Xiaofan Lv; Sheng Zhang; Hanjun Ma; Benguo Liu (Food Chemistry, 2023)

High-resolution mapping of QTL for fatty acid composition in soybean using specific-locus amplified fragment sequencing - Bin Li; Shengxü Fan; Fukuan Yu; Ying Chen; Shengrui Zhang; Fenxia Han; Shurong Yan; Lianzheng Wang; Junming Sun (Theoretical and Applied Genetics, 2017)

Analysis of additive and epistatic quantitative trait loci underlying fatty acid concentrations in soybean seeds across multiple environments - Shengxu Fan; Bin Li; Fukuan Yu; Fenxia Han; Shurong Yan; Lianzheng Wang; Junming Sun (Euphytica, 2015)
Soybean is one of the most important oilseed crops in the world. The soybean oil contains various fatty acids. Their concentrations determine the quality and nutritional value of soybean oil. On the other hand, quantitative trait loci (QTL) mapping for the concentrations of soybean predominant fatty acids could provide the genetic basis for soybean fatty acid composition. In this study, a soybean genetic linkage map was constructed based on 161 polymorphic SSR markers in recombinant inbred lines (RILs) derived from a cross of cv. Luheidou2 × Nanhuizao. By using this map, 35 additive QTLs underlying individual fatty acid concentrations were identified in single environment, while 17 additive QTLs were identified underlying specific fatty acids across multiple environments or underlying multiple fatty acids. Fifteen of the 52 loci were found to be novel loci, explaining 5–24 % of phenotypic variation. Moreover, 25 epistatic QTLs were identified and explained a high phenotypic variation for the fatty acid concentrations, suggesting an essential role of epistatic effect for fatty acid concentrations. The identification of additive and epistatic QTLs suggested a complex network for soybean fatty acid concentrations, and will facilitate the understanding for fatty acid accumulation.